2023
DOI: 10.3389/fpubh.2022.982339
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of research into mental health consumers' perspectives on their physical health: Is there an absence of consumers in the design, conduct, analysis and reporting of this research?

Abstract: We conducted a critical review, using systematic methods, of the literature examining mental health consumer perspectives on their physical and mental health in academic research published between 2005 and 2021. This review examined the inclusion, extent, type and centrality of consumer perspectives regarding their mental and physical health. The search produced 1,865 papers from which 116 met the inclusion criteria. Studies predominantly focused on consumers' individual experiences of their physical and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…women in male-dominated environments, intersex workers) to make sure the objectives and approaches of our interventions match the expressed needs of the relevant workers. Co-design can be espoused, yet is unfortunately sometimes neglected, as an approach to ensure relevant groups are included in the definition of objectives, approaches, delivery and evaluation of interventions (Green et al, 2023; Lam and Pitsaki, 2018; Salmi and Mattelmäki, 2021). Such research methods require that organisational scholars engage in the development of long-term and substantive partnerships with research participants and the organisations they are part of.…”
Section: Looking Ahead: An Academic Agendamentioning
confidence: 99%
“…women in male-dominated environments, intersex workers) to make sure the objectives and approaches of our interventions match the expressed needs of the relevant workers. Co-design can be espoused, yet is unfortunately sometimes neglected, as an approach to ensure relevant groups are included in the definition of objectives, approaches, delivery and evaluation of interventions (Green et al, 2023; Lam and Pitsaki, 2018; Salmi and Mattelmäki, 2021). Such research methods require that organisational scholars engage in the development of long-term and substantive partnerships with research participants and the organisations they are part of.…”
Section: Looking Ahead: An Academic Agendamentioning
confidence: 99%
“…In one study by Nash ( 6 ), people diagnosed with mental illness reported being told by their doctors that they were imagining physical health symptoms for which they were seeking treatment [see also ( 7 , 8 )]. In a review of the literature on the experiences of people diagnosed with mental illness seeing physical healthcare, our team identified that healthcare is a human right, and yet, health systems and professionals fail to ensure this right is actualised ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physical health experiences of women who access mental health services are under researched and under-valued ( 9 ). Women are statistically more likely to experience mental and physical health disablement because their needs as they understand them are misconstrued by practitioners and experiences often psychopathologised ( 10–12 ).…”
Section: Introductionmentioning
confidence: 99%